2017
DOI: 10.1038/s41391-017-0022-9
|View full text |Cite
|
Sign up to set email alerts
|

Convective radiofrequency water vapor thermal therapy for benign prostatic hyperplasia: a single office experience

Abstract: Rezūm radiofrequency water vapor thermal therapy offers a minimally invasive option for BPH management with moderate improvement in symptoms and flow rate. The results appear to be independent of prostate size or presence of a median lobe, and have now been replicated in a single office setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 11 publications
5
72
0
Order By: Relevance
“…Urolift: a single-center retrospective study [10], a multicenter blinded randomized controlled trial (RCT) with 5 year follow-up [11][12][13], a multicenter non-blinded RCT with 2 year follow-up [14,15], a retrospective study with prospectively collected data [16], and a multicenter non-randomized prospective study [17]. Rezūm: a multicenter blinded RCT with 4 year follow-up [18], a cross-over study from the RCT [19], a multicenter retrospective study [20], a single-center retrospective study [21], and a prospective nonrandomized pilot study [22]. Ultimately, a total of 81, 418, and 505 patients were recruited for iTIND, Urolift and Rezūm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Urolift: a single-center retrospective study [10], a multicenter blinded randomized controlled trial (RCT) with 5 year follow-up [11][12][13], a multicenter non-blinded RCT with 2 year follow-up [14,15], a retrospective study with prospectively collected data [16], and a multicenter non-randomized prospective study [17]. Rezūm: a multicenter blinded RCT with 4 year follow-up [18], a cross-over study from the RCT [19], a multicenter retrospective study [20], a single-center retrospective study [21], and a prospective nonrandomized pilot study [22]. Ultimately, a total of 81, 418, and 505 patients were recruited for iTIND, Urolift and Rezūm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Several other studies have reported similar improvements in LUTS due to BPH without a negative impact on sexual function at 1-2 years. 12,13 Early results from the UK were reported at the British Association of Urological Surgeons meeting in 2018 and are due to be presented at the European Association of Urology meeting in 2019. Rezum treatments in the UK have also received positive feedback from patients (see Box 1).…”
Section: Resultsmentioning
confidence: 99%
“…Significantly, sexual function is well preserved after this procedure, with ejactulatory dysfucntion occuring in only 3% of subjects; erectile function impairment was noted only among patients with a previous dysfunction 18, 21 . Among main complications, urinary tract infection occurred in 17% of patients and a transient urinary retention after catheter withdrawn happened in 14% of cases, while other complications such as urethral stenosis occurred in less than 4% of patients 18 . Efficacy of the procedure was not related to prostate volume.…”
Section: Tissue Ablationmentioning
confidence: 98%
“…Patients are discharged on the same day of the procedure and should keep an indwelling bladder catheter for 1 week. Available studies to date have demonstrated that, after procedure, there is an increase in urinary flow rate of up to 6 milliliters per second, as well as a 11-point improvement of symptoms as evaluated with the IPSS 18,19 . So far, efficacy of the results has been demonstrated at the end of a 2-year follow-up 19 .…”
Section: Tissue Ablationmentioning
confidence: 99%
See 1 more Smart Citation